Kampanye Generasi Sehat: Meningkatkan Kesadaran Dan Pengetahuan Remaja Tentang Stunting - Andy Muharry; Nissa Noor Anashr; Dadan Yogaswara; Faisal Fadila Noorikhsan (Lembaga Pengembangan Kinerja Dosen, 2023)
Tasikmalaya is one of the areas that has a fairly high prevalence of stunting, 28.9% in 2021. Meanwhile, in 2022 stunting in the city of Tasikmalaya ranks fifth highest in West Java. Lack of understanding about nutrition and parenting can increase the risk of stunting. Adolescence is a phase in human life that needs to be protected from the risk of health problems so that in the future they can take prevention as early as possible. The purpose of this activity is to increase youth's knowledge about stunting and its prevention. This community service activity is carried out through four stages, namely 1) identifying problems together with partners, 2) determining solutions and activity plans, 3) implementing educational activities, 4) conducting evaluations with pre-tests and post-tests. Educational activities are carried out by providing material about stunting and its relationship with adolescents as well as the practice of measuring nutritional status. This activity involved 56 participants. The results of the activity showed that the knowledge of adolescents before being given education was 57.30 while after being given education it was 73.92. There was an increase in the average knowledge score of 16.67. Furthermore, the results of statistical tests using paired t-test obtained results, p = 0.0000 <0.005. It can be concluded that there is a significant difference in knowledge before and after stunting education is carried out for students at At Taufiq Middle School and High School, Tasikmalaya City.